Severe acute respiratory infections treatment centre : practical manual to set up and manage a severe acute respiratory infection SARI treatment centre and a SARI screening facility in health care facilities (World Health Organization, 2020)
This is the first edition of the practical manual to set up and manage a severe acute respiratory infection (SARI) treatment centre and a SARI screening facility in health-care facilities. The document has been developed to meet the operational needs emerging with the COVID-19 pandemic.
Keywords: větrání; Coronavirus Infections; kontrola infekce; veřejné zdravotnictví; prostředí kontrolované; epidemie; izolace pacientů; infekční lékařství; zdravotní péče - zařízení, personál a služby; koronavirové infekce; COVID-19; zásobování vodou; Disease Outbreaks; Health Care Facilities Workforce and Services; pneumologie a ftizeologie; syndrom akutního respiračního selhání; Epidemics; Infection Control; epidemický výskyt choroby; Water Supply; Ventilation; Severe Acute Respiratory Syndrome; Environment, Controlled; Patient Isolation